Application of lean thinking approach to an internal service system of a utilities company - Machado, João Pedro Ferreira (2014)
An ineffective and inefficient provision of internal services has impacts on the performance and sustainability of organisations. The current research aims at verifying if effectiveness and efficiency gains result from the application of a systematic lean approach to the internal services of a utilities company. Lean thinking is the conceptual framework considered for such purpose. The methodology serving such intents is based on a case study developed at the markets division of a utilities company with business on the power and gas markets. The information that sustains this research was collected through direct observation and informal interviewing of the staff of the markets division, as well as of its internal customers. The lean thinking systematic approach encompasses the application of lean tools. In this regard, process activity mapping is employed, as well as other lean tools, like problem solving, kaizen blitz events, kanban, or work standardisation. Three processes concurring to the provision of internal services are studied: market risk hedging, database parameterisation for financial derivatives register, and CO2 emission allowances stock calculation. The assessment of such processes within a lean thinking tools framework and their customer value and waste identification are followed by the implementation of improved versions of such processes. Results indicate that effectiveness gains are achievable and carry real impacts in terms of value for the internal customer, an aspect sparsely developed on previous research. In terms of efficiency impacts, lead time is reduced 74%, 97% and 89% for each process, respectively, whilst personnel participation is reduced 7%, 20% and 57%.